Different training systems for Physalis peruviana L. in Southern Brazil - Muniz J.* (2012)
The cape gooseberry (Physalis peruviana L.) is native of South America, the center of origin and diversity is located at the Andean zone between Colombia, Peru and Ecuador. This fruit crop shows good perspectives to commercial use. The objective of this work was to evaluate different training systems for physalis in Southern Brazil. The experiment was conducted in the city of Lages (27°48'S; 50°19'W, altitude 916 m). Four training systems were tested, vertical shoot positioning trellis, "X", "V" and the control without training system. The spacing was 3.0 m between-rows and 1.0 m within-row. The variables evaluated were productivity (t ha-1), weight (g) and diameter (mm) of fruits, total soluble solids (TSS), pH and acidity (meq L-1). The experimental design was completely randomized, data were submitted to analysis of variance and Tukey's test (5% probability). The training system influenced plant development and fruit quality. To productivity and fruit weight, the best results observed were on vertical shoot positioning trellis followed by "V". For fruit diameter, vertical shoot positioning trellis and "X" did not differ and produced the biggest fruits. The control followed by vertical shoot positioning trellis presented the best TSS/acidity ratio. The variable pH showed no significant difference between treatments. Higher quality fruits were produced in plants with lower stem density.